2020
DOI: 10.1016/j.clnu.2019.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of a rapid sarcopenia measure in acutely ill older adults

Abstract: Background: Current recommendations to assess sarcopenia requiring specialized equipment hinder its use as a prognostic tool in busy acute settings. Aims:To investigate the prognostic value of a rapid sarcopenia measure in acutely ill older outpatients for 1-year adverse outcomes. Methods:Prospective study with 665 acutely ill older adults (mean age 78.7±8.3 years; 63% women) in need of intensive management to avoid hospital admission. Sarcopenia was screened upon admission, defined as the presence of both low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 48 publications
2
15
0
3
Order By: Relevance
“…Calf circumference measure has been used to estimate muscle mass in the elderly in clinical practice and has a good correlation with gold standard methods even for younger populations. 12 , 13 Studies indicate that the measure is able to predict hospital readmission in adults 14 and survival among the elderly. 15 Our study found correlation between calf circumference and the variables related to HIV, in addition to similar results in the staging of sarcopenia when compared to bioimpedance.…”
mentioning
confidence: 99%
“…Calf circumference measure has been used to estimate muscle mass in the elderly in clinical practice and has a good correlation with gold standard methods even for younger populations. 12 , 13 Studies indicate that the measure is able to predict hospital readmission in adults 14 and survival among the elderly. 15 Our study found correlation between calf circumference and the variables related to HIV, in addition to similar results in the staging of sarcopenia when compared to bioimpedance.…”
mentioning
confidence: 99%
“…Our study indicated that low handgrip strength could be an independent predictor for mortality among Chinese inpatients, which is consistent with other previously published studies ( 12 , 41 ). Handgrip strength can be obtained by using simple equipment that is not time-consuming to use and can be applied in any clinical setting, which is very convenient for medical staff ( 42 ). In addition, according to the EWGSOP2 recommendation, muscle strength is a core component of screening for sarcopenia, because it can reflect key features of the disease, and has been reported to accompany an increased risk of adverse outcomes ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“… 30 On the other hand, some studies used the standard definition of sarcopenia (<34 cm for men and <33 cm for women). 31 We suspect this is partly the reason that inconsistent results were generated when using different cutoff values.…”
Section: Discussionmentioning
confidence: 99%
“…de Sousa et al 26 also reported similar results among older adults with Alzheimer’s disease. Whereas, recently, Aliberti et al 31 reported that low muscle mass assessed by CC (<33 cm for women or <34 cm for men) was not associated with an increased risk of mortality. A similar study was conducted by Tarnowski et al, 24 who reported that low CC did not significantly increase the risk of mortality among emergency patients.…”
Section: Introductionmentioning
confidence: 93%